1991
DOI: 10.1007/bf00053126
|View full text |Cite
|
Sign up to set email alerts
|

Adult dietary intake and prostate cancer risk in Utah: a case-control study with special emphasis on aggressive tumors

Abstract: A population-based case-control study in Utah of 358 cases diagnosed with prostate cancer between 1984 and 1985, and 679 controls categorically matched by age and county of residence, were interviewed to investigate the association between dietary intake of energy (kcal), fat, protein, vitamin A, beta-carotene, vitamin C, zinc, cadmium, selenium, and prostate cancer. Dietary data were ascertained using a quantitative food-frequency questionnaire. Data were analyzed separately by age (45-67, 68-74) and by tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
204
3
9

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(229 citation statements)
references
References 46 publications
11
204
3
9
Order By: Relevance
“…These chemicals have proved to be associated with cancers at other sites (De Stefani et al, 1997) and further studies on prostate cancer and heterocyclic amine intake are needed. Total fat intake was associated with risk in our study as in previous studies (West et al, 1991;Giovannucci et al, 1993;Whittemore et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These chemicals have proved to be associated with cancers at other sites (De Stefani et al, 1997) and further studies on prostate cancer and heterocyclic amine intake are needed. Total fat intake was associated with risk in our study as in previous studies (West et al, 1991;Giovannucci et al, 1993;Whittemore et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…The risk associated with fat intake was more evident among obese patients, and also after controlling for dietary fibre and vitamin E intakes (results not shown). As in previous studies (West et al, 1991;Rohan et al, 1995;Whittemore et al, 1995;Meyer et al, 1997), total energy intake was a risk factor for prostate cancer.…”
Section: Discussionsupporting
confidence: 72%
“…[13][14][15] Whereas increased intraprostatic cholesterol levels have been associated with malignancy, 29 cholesterol increases in tumor tissue likely occur by complex mechanisms that are inadequately mirrored by serum cholesterol. Furthermore, we found no association between BMI and the development of PC.…”
Section: Discussionmentioning
confidence: 99%
“…11 The Norwegian study found a positive association between a-linolenic acid and PC risk and an inverse association between the ratio of linoleic (from non-animal fat) to a-linolenic acid and PC. 12 Cholesterol has also been examined in dietary studies, and a positive association with PC was reported in two case-control studies that did not adjust for energy intake, 13,14 whereas no such correlation was found in a Swedish study that did adjust for energy intake. 15 Overall, there is a high degree of consistency with regard to consumption of animal fat, particularly red meat, and PC.…”
Section: Introductionmentioning
confidence: 99%
“…More than half the studies in this area show an inverse relationship between physical activity and PC, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] other studies show no association [31][32][33][34][35][36][37][38][39][40][41][42] and four studies even found exercise increased PC risk. [43][44][45][46] Perhaps this uncertainty in the literature can be attributed to the epidemiological nature of the research designs utilized in these studies, which relied upon survey or patient self-reporting to elicit physical activity and/or exercise exposure. In addition, many of these studies made no distinctions about the type of physical activity that respondents were performing and few validated physical activity exposure with objective measurements of fitness (that is, cardiorespiratory fitness testing).…”
Section: Exercise and Prostate Cancer Preventionmentioning
confidence: 99%